'National indifference' in the Baltic territories? A critical assessment. Issue 1 (2nd January 2017) - Bolin, Per; Douglas, Christina
ABSTRACT: Tara Zahra maintains in her article 'Imagined Noncommunities: National Indifference as a Category of Analysis' that many people in the early twentieth century were indifferent to the call of the national movements or oscillated between different national belongings. While finding Zahra's perspective relevant, this article criticizes the choice of her central analytic concept, 'national indifference, ' and also questions the absence of an integrated gender perspective. Finally, the article queries the general applicability of her theoretical approach. While useful in the analysis of demotic national movements, it is considerably less so when studying elite minority groups. This becomes evident when Zahra's theoretical perspective is applied to the Baltic Germans.